Identification of Heading Date Six (Hd6) Gene Derived from Rice Mutant Varieties - Aryanti Aryanti; Ita Dwimahyani; Ishak Ishak (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2017)
Genes which were associated with flowering time to indicate the early maturity is known as heading date (Hd). Heading date six (Hd6) gene was identified from rice mutant varieties were Atomita 2, Atomita 3, Atomita 4, Bestari, Cilosari, Diah Suci, Sidenuk, Kahayan, Mayang, Meraoke, Mira-1, Pandan Putri, Superwin, Suluttan Unsrat 1, Suluttan Unsrat 2, Winongo, Woyla, Yuwono, while the rice var. Nipponbare was used as a positive control. All of rice mutant varieties derived from mutation induction by the dose of 0.2 kGy. The aim of this experiment was to find out the data base of mutant varieties which could be used as parent material with earlier maturity trait genetically. To obtain the DNA of plants, young leaves of each variety were extracted by liquid nitrogen, and then lysis and extracted by Kit Plant Genomic DNA. The amplification of DNA with 7 primers of Hd6 conducted of 40 cycles by PCR and were continues to separated by 1 % agarose. The results were shown that the rice Mira-1 and Bestari varieties obtained from mutation of Cisantana highly different from one to another on 7 primers of Hd6 used. Mayang variety from mutation of cross breeding between Cilosari and IR64, Pandan putri from Pandan wangi and Woyla from mutation of cross breeding from Atomita 2 and IR64 were highly different with those of their parents. Identification of Hd6 gene on Sidenuk variety was shown the same bands pattern with Nipponbare as control positive toward all primers used, this variety would be better for earlier maturity parent material compared to others. The information could be useful for breeding programs aiming to develop early maturing widely adaptive and high yielding rice cultivars.